Phase Control Implementation in an UWB Hyperthermia Prototype System - Kihlström, Tobias; Broman, Simon (My University, 2025)
This degree project investigates the implementation of phase regulation in a prototype ultra-wideband (UWB) hyperthermia system developed at Chalmers. A proportional control algorithm was integrated using an AD8302 gain and phase detector, with calibration performed to relate voltage outputs to known phase differences. The system was tested in an emulated feedback loop using MATLAB and Arduino to control digital phase shifters. Testing at 650 MHz demonstrated optimal performance, while results at 300 MHz and 900 MHz revealed incomplete or irregular phase shifts. Although verification relied on visual inspection due to limited measurement equipment, the regulator successfully adjusted signal phases towards defined targets. Further improvements are required to achieve higher precision and system reliability.
Keywords: Hyperthermia; Medical; Device; Proportional; Regulator; Phase; AD8302